Education in the Midst of Indonesia's Development Agenda - Fitramadhana, Rizqyansyah (Universitas Negeri Malang, 2023)
President Jokowi made a shocking decision in his second term by pointing to Nadiem Makarim as Minister of Education, Culture, Research, and Technology. Not long after his appointment, Nadiem Makarim released Merdeka Belajar and Peta Jalan Pendidikan Indonesia 2020-2035, which is significant to Indonesia’s education context. Those two stipulations alone indicate exponential change within education governance in Indonesia. Various notable scholars later argue that Nadiem Makarim’s policy is intriguing and essential, emphasizing their support for Merdeka Belajar and Peta Jalan Pendidikan Indonesia 2020-2035. A glance at scientific articles published right after enacting these two policies shows that many, if not most, researchers agree thoroughly with Nadiem Makarim. In contrast with the previous undertaking, this study uses critical explanations to expose and unearth the interest lurking beneath the so-called neutral policy agenda. To support the aim of this research, a critical policy study paradigm will be used along with the critical discourse analysis of Norman Fairclough. There are two significant findings from an in-depth search of the study of the text production process, text analysis, and interpretation of discourse and social practices of education policy during the Jokowi era. First, in the eye of Jokowi’s administration, education is part of the development business. Education, in short, is seen as a proper tool (a) to adapt to the current condition of the knowledge-based economy and to cultivate human resources and (b) to build a young generation (Profil Pelajar Pancasila) who can thrive in the changing world without losing its grip on Pancasila as the main symbol of Indonesia. Second, Jokowi’s education discourses and social practices are spurred by the urgent need to reskill, upskill, and enhance the employability of both workers and future workers. These two propositions are corroborated by the production of texts that are thick with institutional interests in the form of increasing human capital for Indonesia's Vision 2045, text analysis that shows the dominance of representation of human resource development interests in various policy documents in Indonesia, and interpretation of discourse that hints at the existence of link and match hegemony in human resource development projects as well as efforts to align cognitive and ethical aspects through the P5 program.Pendidikan di Dalam Agenda Pembangunan IndonesiaPada periode kedua pemerintahannya, Presiden Jokowi melakukan gebrakan dalam dunia pendidikan dengan menunjuk Nadiem Makarim sebagai Mendikbudristek. Tak lama berselang, Nadiem Makarim meresmikan kebijakan Merdeka Belajar serta merintis Peta Jalan Pendidikan Indonesia 2020-2035 yang sangat signifikan bagi lanskap pendidikan di Indonesia. Dua momen tersebut menandakan sebuah perubahan seismik dalam tata kelola pendidikan di Indonesia. Menanggapi terobosan itu banyak pihak menyatakan dukungannya. Artikel ilmiah yang terbit setelah Merdeka Belajar diresmikan lebih banyak berpihak pada upaya pemerintah. Berlawanan dengan tren tersebut, kajian ini mencoba menghadirkan pembahasan kritis mengenai kebijakan pendidikan di masa Jokowi—khususnya pada periode kedua pemerintahannya. Untuk mendukung tujuannya, penelitian ini menggunakan paradigma studi kebijakan kritis yang dikombinasikan dengan metodologi analisis wacana kritis milik Norman Fairclough. Dari penelusuran mendalam tentang studi terhadap proses produksi teks, analisis teks, dan interpretasi wacana serta praktik sosial kebijakan pendidikan pada masa Jokowi, terdapat dua temuan penting. Pertama, dalam agenda pembangunan Indonesia, pendidikan diposisikan sebagai (a) alat untuk menyesuaikan diri dengan ekonomi berbasis pengetahuan dan menciptakan sumber daya manusia unggul (b) serta membangun Profil Pelajar Pancasila yang atentif terhadap perkembangan zaman dan peduli pada pelestarian identitas khas bangsa Indonesia. Kedua, diskursus dan praktik sosial pendidikan tersebut digulirkan agar pekerja dan calon pekerja dapat beradaptasi dengan profil keterampilan baru. Dua proposisi tersebut dibuktikan oleh produksi teks yang kental dengan kepentingan institusional berupa peningkatan sumber daya manusia unggul untuk Visi Indonesia 2045, analisis teks yang menunjukkan dominasi representasi kepentingan pembangunan sumber daya manusia dalam berbagai dokumen kebijakan di Indonesia, dan interpretasi wacana yang mengisyaratkan eksistensi hegemoni link and match dalam proyek pembangunan sumber daya manusia serta upaya penyelarasan aspek kognitif dan budi pekerti lewat program P5.